Analisis Pengendalian Internal Berbasis COSO Terhadap Penilaian Kinerja Karyawan pada PT.BPRS Sarana Prima Mandiri Pamekasan - Ria Rachmawati; Farah Ummu Nabila (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
This study aims to make PT. Sharia People Development Bank (BPRS) Sarana Prima Mandiri is able to carry out COSO-based internal control in which there are 5 elements consisting of control environment, risk assessment, control activities, monitoring, information and communication. To test the effect on employee performance appraisal, hypothesis testing will be conducted. Data collection using a questionnaire with a purposive sampling method that is sampling based on criteria distributed to 62 employees of PT. SRB Sarana Prima Mandiri Pamekasan who became the study sample. Data analysis uses the classical assumption test, multiple linear regression, and the coefficient of determination (R2) which is processed by the SPSS program. The result is a control environment partially influences employee performance appraisal, risk assessment partially influences employee performance appraisal, control activities partially influences employee performance appraisal, monitoring partially influences employee performance appraisal, information and communication partially influences performance appraisal employees (t test), whereas in (F test) control environment, risk assessment, control activities, monitoring, information and communication simultaneously influence employee performance appraisal.Keywords: Internal Control ; COSO ; Employee Performance Evaluation.